(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article emphasizes the importance of the use of information technology in the organization of physical education and sports lessons in higher education, the formation of worldview and thinking, the formation of physical, spiritual and moral qualities, the future of physical education and the teaching of physical education and sports.